FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT STRES AKADEMIK MAHASISWA UNIVERSITAS CITRA BANGSA KUPANG SELAMA PANDEMI VIRUS CORONA - Delia Da Silva; Balbina Antonelda M Wawo; Aysanti Yuliana Paulus (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2022)
The spread of the corona virus has had a major impact on changing learning methods, from offline to online by utilizing internet access. Monotonous situations, too many assignments, lack of understanding of the material presented by lecturers, as well as networks that are not always good and limited internet quotas have a serious impact on students who have the potential to experience stress. The purpose of this study was to determine the factors that related to the level of academic stress of students at the Citra Bangsa University Kupang during the Corona Virus pandemic. This research method is quantitative research with a correlational design, a cross-sectional approach, a sample of 206 students of the class of 2020 at the Citra Bangsa University Kupang using a quota sampling technique with a statistical analysis test used, namely the chi-square test. The results showed that there was no relationship between the learning task factor and the student's academic stress level (p-value 0.178 > 0.05), there was no relationship between the boredom factor at home and the students' academic stress level (p-value 0.703 > 0.05), no the relationship between internet quota factors and students' academic stress levels (p-value 0.359 > 0.05), there is no relationship between online learning factors and students' academic stress levels (p-value 0.440 > 0.05). Conclusion: The condition of students' academic stress levels during the corona virus pandemic at Citra Bangsa University was not caused by the learning task factor, the boredom factor at home, the internet quota factor, and the online learning factor. Keywords: Students, Academic Stress Level, Corona Virus